2016
DOI: 10.1111/cogs.12352
|View full text |Cite
|
Sign up to set email alerts
|

The Interdisciplinarity of Collaborations in Cognitive Science

Abstract: We introduce a new metric for interdisciplinarity, based on co-author publication history. A published article that has co-authors with quite different publication histories can be deemed relatively "interdisciplinary," in that the article reflects a convergence of previous research in distinct sets of publication outlets. In recent work, we have shown that this interdisciplinarity metric can predict citations. Here, we show that the journal Cognitive Science tends to contain collaborations that are relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
0
26
0
3
Order By: Relevance
“…But a case could certainly be made for using other measures. Zhang, Rousseau, and Glanzel [ 33 ], for example, argue for using their D2S measure that emphasizes variety over disparity and balance as an indicator of interdisciplinary diversity, and Bergmann and his colleagues [ 34 ] argue for quantifying interdisciplinarity by means of Jenson-Shannon divergence. Nonetheless, as suggested by our admittedly rough calculation of citation out of field and our qualitative comparison of the top cited and citing journals, the differences in integration and diffusion between the articles in Nature and Science and those in the disciplinary journals were not great.…”
Section: Discussionmentioning
confidence: 99%
“…But a case could certainly be made for using other measures. Zhang, Rousseau, and Glanzel [ 33 ], for example, argue for using their D2S measure that emphasizes variety over disparity and balance as an indicator of interdisciplinary diversity, and Bergmann and his colleagues [ 34 ] argue for quantifying interdisciplinarity by means of Jenson-Shannon divergence. Nonetheless, as suggested by our admittedly rough calculation of citation out of field and our qualitative comparison of the top cited and citing journals, the differences in integration and diffusion between the articles in Nature and Science and those in the disciplinary journals were not great.…”
Section: Discussionmentioning
confidence: 99%
“…The Solomon et al study also demonstrated that, as measured by their cited references, the articles in Science and Nature studied within each of the fields "are not significantly more interdisciplinary than are those sampled in the disciplinary journals" (for instance, the journal Cognitive Science). Bergmann, Dale, Sattari, Heit & Bhat (2016), also focusing on the journal Cognitive Science, discussed another new metric for interdisciplinarity, based on co-author publication history.…”
Section: Interdisciplinary Research and Collaboration In Psychologymentioning
confidence: 99%
“…Scores on interdisciplinarity are then compared to other scientific fields and journals, especially within a group of cognitive science and neuroscience journals. (Bergmann et al, 2016) Porter and Rafols (2009) looked at Neurosciences and five other research domains (all subject categories in Web of Science) to see whether science was becoming more interdisciplinary over the thirty-year span from 1975-2005. Using a "combination of interdisciplinary metrics with science mapping enables us to characterize research interdisciplinarity with a detail not previously available" (p. 740) and it was concluded that "science is indeed becoming more interdisciplinary, but in small steps.…”
Section: Interdisciplinary Research and Collaboration In Psychologymentioning
confidence: 99%
“…The construction of a research activity profile analiza principalmente la producción científica de las personas (Bergmann, Dale, Sattari, Heit & Bhat, 2016) o centros especializados en investigación, de tal forma que, estudiando el currículum de estas personas y centros dedicados a un campo especializado, se puede apreciar y cuantificar la diversidad de sub-disciplinas ajenas que se utilizan en el estudio de una determinada área científica. Por ejemplo, se espera que un centro especializado en Psicología produzca principalmente en esta área, pero también es cierto que, por afinidad, un investigador del área produzca trabajos en áreas afines como como Medicina, Sociología, Comunicación, etc.…”
Section: Introductionunclassified